Defining Global Benchmarks in Bariatric Surgery: A Retrospective Multicenter Analysis of Minimally Invasive Roux-en-Y Gastric Bypass and Sleeve Gastrectomy. Issue 5 (November 2019) - Gero, Daniel; Raptis, Dimitri A.; Vleeschouwers, Wouter; van Veldhuisen, Sophie L.; Martin, Andres San; Xiao, Yao; Galvao, Manoela; Giorgi, Marcoandrea; Benois, Marine; Espinoza, Felipe; Hollyman, Marianne; Lloyd, Aaron; et al.
Abstract : Objective: To define "best possible" outcomes for bariatric surgery (BS)(Roux-en-Y gastric bypass [RYGB] and sleeve gastrectomy [SG]). Background: Reference values for optimal surgical outcomes in well-defined low-risk bariatric patients have not been established so far. Consequently, outcome comparison across centers and over time is impeded by heterogeneity in case-mix. Methods: Out of 39, 424 elective BS performed in 19 high-volume academic centers from 3 continents between June 2012 and May 2017, we identified 4120 RYGB and 1457 SG low-risk cases defined by absence of previous abdominal surgery, concomitant procedures, diabetes mellitus, sleep apnea, cardiopathy, renal insufficiency, inflammatory bowel disease, immunosuppression, anticoagulation, BMI>50 kg/m 2 and age>65 years. We chose clinically relevant endpoints covering the intra- and postoperative course. Complications were graded by severity using the comprehensive complication index. Benchmark values were defined as the 75th percentile of the participating centers' median values for respective quality indicators. Results: Patients were mainly females (78%), aged 38±11 years, with a baseline BMI 40.8 ± 5.8 kg/m 2 . Over 90 days, 7.2% of RYGB and 6.2% of SG patients presented at least 1 complication and no patients died (mortality in nonbenchmark cases: 0.06%). The most frequent reasons for readmission after 90-days following both procedures were symptomatic cholelithiasis and abdominal pain of unknown origin. Benchmark values for both RYGB and SG at 90-days postoperatively were 5.5% Clavien-Dindo grade ≥IIIa complication rate, 5.5% readmission rate, and comprehensive complication index ⩽33.73 in the subgroup of patients presenting at least 1 grade ≥II complication. Conclusion: Benchmark cutoffs targeting perioperative outcomes in BS offer a new tool in surgical quality-metrics and may be implemented in quality-improvement cycle. ClinicalTrials.gov Identifier NCT03440138 Abstract : Supplemental Digital Content is available in the text